Microwave Ablation Combined with Flt3L Provokes Tumor‐Specific Memory CD8+ T Cells‐Mediated Antitumor Immunity in Response to PD‐1 Blockade - Meixiang Wang; Jing Sang; Fengkuo Xu; Shulong Wang; Peng Liu; Ji Ma; Zhengtao Chen; Qi Xie; Zhigang Wei; Xin Ye (Advanced Science)
Abstract For medically inoperable non‐small cell lung cancer, microwave ablation (MWA) represents a super minimally invasive alternative treatment. However, tumor recurrence remains a concern. Here, it is demonstrated that the combination of MWA with Flt3L significantly inhibits tumor recurrence by CD8+ central memory T (TCM)‐like cell‐dependent antitumor immune responses within the tumor‐draining lymph nodes (TdLN). TdLN‐TCM‐like cells encompassed both tumor‐specific memory T (TTSM) and progenitor‐exhausted T (TPEX) cells. The expansion of these cells markedly altered the differentiation of exhausted T cells within the tumor microenvironment (TME). TPEX predominantly differentiated into transitory effector‐like exhausted T cells (TEX‐int). The expansion of TTSM cells elicited by the combined therapy was reliant on conventional dendritic cells (cDCs) and was likely specifically dependent on the migratory cDC1s (Mig cDC1s) within the TdLN. The upregulation of ICOSL on migratory cDC1s was pivotal in initiating TTSM‐like cell‐mediated antitumor responses. Slc38a2 may be a critical gene responsible for the upregulation of ICOSL in Mig cDC1s following combined treatment. Finally, the combined treatment significantly enhanced the antitumor efficacy of immunotherapy based on PD‐1 blockade. The research thereby afforded a novel strategic approach to forestall tumor recurrence after MWA therapy, while also providing the foundational proof‐of‐concept for impending clinical investigations.